2010
DOI: 10.1186/1465-9921-11-92
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influence on lung function impairment in Swedish twins

Abstract: BackgroundThe understanding of the influence of smoking and sex on lung function and symptoms is important for understanding diseases such as COPD. The influence of both genes and environment on lung function, smoking behaviour and the presence of respiratory symptoms has previously been demonstrated for each of these separately. Hence, smoking can influence lung function by co-varying not only as an environmental factor, but also by shared genetic pathways. Therefore, the objective was to evaluate heritabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 24 publications
3
25
1
Order By: Relevance
“…This sample size is hardly sufficient for the modern variance component models we have applied. Results from a relatively small-sized twin study tried to address the question of sex differences in heritability of FEV 1 and FVC by using variance components analysis and found sex differences in the genetic contribution to FEV 1 with heritability being nonsignificant for males [22]. That study, however, consisted of only 176 complete twin pairs compared to the more than 1,500 complete pairs in our study, and the selection criteria of that study were based on the presence of respiratory symptoms [22] which differed from our study.…”
Section: Discussionmentioning
confidence: 99%
“…This sample size is hardly sufficient for the modern variance component models we have applied. Results from a relatively small-sized twin study tried to address the question of sex differences in heritability of FEV 1 and FVC by using variance components analysis and found sex differences in the genetic contribution to FEV 1 with heritability being nonsignificant for males [22]. That study, however, consisted of only 176 complete twin pairs compared to the more than 1,500 complete pairs in our study, and the selection criteria of that study were based on the presence of respiratory symptoms [22] which differed from our study.…”
Section: Discussionmentioning
confidence: 99%
“…These twins were invited to participate in more indepth measures of lung function. The selection of subjects was initially conducted for a heritability study, as described previously, in a manner such that disease-concordant and -discordant twins were prioritised over symptom-free twin pairs [15]. The selection was also based on feasibility aspects, such as geography, budget and personnel.…”
Section: Study Populationmentioning
confidence: 99%
“…Genetics affects both smoking and body composition (Ordonana et al, 2007;Vink et al, 2005), and together with age, they comprise the main factors modifying lung function heritability (Amara et al, 2001;Hallberg et al, 2010;Wilk et al, 2000). Previous studies on lung function heritability are cross-sectional and include smokers and non-smokers.…”
mentioning
confidence: 99%
“…estimated multivariate-adjusted heritabilities are 40%-65% for FEV1, 40%-55% for FVC, and 45% for FEV1/FVC ratio (Hallberg et al, 2010;McClearn et al, 1994;Palmer et al, 2001;Wilk et al, 2000). Genome-wide association (GWA) studies have identified multiple single-nucleotide polymorphisms (SNPs) associated with lung function (Hancock et al, 2010;Repapi et al, 2010).…”
mentioning
confidence: 99%